2020
DOI: 10.1002/adfm.202000034
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Additive Low‐Dimensional Ruddlesden–Popper Perovskite by the Incorporation of Glycine Hydrochloride for High‐Performance and Stable Solar Cells

Abstract: The recent rise of low-dimensional Ruddlesden-Popper (RP) perovskites is notable for superior humidity stability, however they suffer from low power conversion efficiency (PCE). Suitable organic spacer cations with special properties display a critical effect on the performance and stability of perovskite solar cells (PSCs). Herein, a new strategy of designing self-additive lowdimensional RP perovskites is first proposed by employing a glycine salt (Gly + ) with outstanding additive effect to improve the photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 50 publications
3
50
0
Order By: Relevance
“…The higher value of MAPbI 3 –SDBS film (45.14) than MAPbI 3 film (3.42) indicated that larger grain could be obtained after doping SDBS. [ 54,55 ] This result is consistent with SEM result. Simultaneously, there are no obvious diffraction peak shifts, which signifies that SDBS does not insert in the MAPbI 3 crystal lattice and not participate in formation of MAPbI 3 lattice, but only probably exists at the GBs.…”
Section: Resultssupporting
confidence: 89%
“…The higher value of MAPbI 3 –SDBS film (45.14) than MAPbI 3 film (3.42) indicated that larger grain could be obtained after doping SDBS. [ 54,55 ] This result is consistent with SEM result. Simultaneously, there are no obvious diffraction peak shifts, which signifies that SDBS does not insert in the MAPbI 3 crystal lattice and not participate in formation of MAPbI 3 lattice, but only probably exists at the GBs.…”
Section: Resultssupporting
confidence: 89%
“…In comparison with typical BA‐based RP perovskites, the Gly‐induced RP perovskites exhibited narrower bandgap, stronger light absorption, longer charge carrier lifetime, and fewer trap densities (Figure 8f(i)–(iv)). [ 128 ] All these desirable optoelectrical properties can be credited to the better film quality obtained by Gly‐based RP perovskites. In this scenario, the CO in Gly endowed it with the strong interaction with Pb 2+ , which drives Gly to become a nucleation center to promote the uniform and fast growth of the Gly‐based RP perovskites.…”
Section: Strategies To Fabricate High‐quality Rp Perovskite Film In Pscsmentioning
confidence: 99%
“…Consequently, the PSCs of the n = 8 and n = 4 Gly‐based RP perovskites delivered PCEs of 15.61% and 18.06%, respectively, with superior long‐term stability against humidity, heat, and even UV light. [ 128 ] In summary, special functional group of organic space cations will open up a new avenue to fabricate high‐quality RP perovskite films via their unique characteristics such as the strong dipole field, electronegativity, and interaction with Pb 2+ .…”
Section: Strategies To Fabricate High‐quality Rp Perovskite Film In Pscsmentioning
confidence: 99%
“…[ 24–27 ] In addition, low‐dimensional PSCs have been reported to possess suppressed hysteresis due to their significant decrease of the inherent structural disorder and orientation randomness. [ 28 ] The introduction of the 2D perovskite at the interface of 3D perovskite and hole transport layer (HTL) could efficiently modify the interface and passivate defect sites, which simultaneously possesses the inherent stability of 2D perovskite and excellent charge transport properties of the 3D perovskite. [ 28,29 ] The functional groups of ammonium salts in 2D perovskites play an important role for passivating defects.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28 ] The introduction of the 2D perovskite at the interface of 3D perovskite and hole transport layer (HTL) could efficiently modify the interface and passivate defect sites, which simultaneously possesses the inherent stability of 2D perovskite and excellent charge transport properties of the 3D perovskite. [ 28,29 ] The functional groups of ammonium salts in 2D perovskites play an important role for passivating defects. Hu et al incorporated S‐benzyl‐L‐cysteine with amine and carboxyl groups to the 2D/3D heterostructure perovskite and impressively obtained high‐quality PSCs.…”
Section: Introductionmentioning
confidence: 99%